Educação física e interculturalidade : formação continuada e colaborativa no contexto xavantinense - Oliveira, Davidson Ferreira (2025)
This research explores the intersection between Physical Education and Interculturality, focusing on the continuing and collaborative training of teachers with the aim of fostering a pedagogical practice that promotes interculturality in the school context. The study was conducted with Physical Education teachers from non indigenous urban schools that serve students of the Xavante ethnic group in the city of Nova Xavantina-MT. The main objective is to investigate the perception and experience of teachers in relation to the valorization of indigenous culture and the promotion of interculturality in the school environment, identifying the desires and challenges in the construction of welcoming and participatory spaces. Methodologically, the research adopts a qualitative approach, being an action research with collaborative inspiration, based on Ibiapina (2008), using cycles of reflections among teachers to analyze, reflect and improve their pedagogical practices. The training sessions were structured to encourage discussions on interculturality, as well as on the legal and pedagogical aspects of Physical Education, with references to authors such as Fensterseifer and González (2020), Candau (2008), Walsh (2009), Neira (2009), among others. Throughout these cycles, teachers reflected on their current practices, discussed the challenges faced, and proposed solutions to promote more participatory and intercultural education. In addition to the reflection cycles, initial and final interviews were conducted to collect data, with analysis following a descriptive approach of the participants' responses. The interviews allowed us to understand the perspectives, experiences, and challenges of teachers in relation to the appreciation of indigenous culture and the promotion of interculturality. The results indicated that, despite the difficulties faced, there is a growing commitment among teachers to integrate practices that respect and value multiple cultures. Thus, the research shows that the ongoing training of Physical Education teachers is an essential component for promoting interculturality in schools. Through critical reflection and pedagogical practices that value indigenous culture, it is possible to build a more just and equitable education. Therefore, this research serves as a call to action for teachers and managers, so that the search for a pedagogical practice that respects and values interculturality becomes a collective goal, contributing to the formation of more aware, respectful citizens who are engaged in the construction of a plural and equitable society.